2009
DOI: 10.1111/j.1469-8137.2009.03094.x
|View full text |Cite
|
Sign up to set email alerts
|

Macroecological patterns of genetic structure and diversity in the aquatic mossPlatyhypnidium riparioides

Abstract: Summary Genetic diversity and structure are described in the aquatic moss Platyhypnidium riparioides to assess its dispersal ability at a regional scale and to determine whether patterns of genetic differentiation correlate with environmental variation. Variation at six nuclear microsatellite loci from 50 populations in southern Belgium was investigated through Mantel tests, partial Mantel tests and spatial analysis of molecular variance. Overall patterns of genotypic variation showed strong differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 102 publications
6
43
0
Order By: Relevance
“…First, variation in spatial heterogeneity and habitat diversity of freshwater systems, which was identified as one of the main drivers of genetic diversification in P. riparioides (19), is lower in Macaronesian islands than on the continent, due to their volcanic origin and the physical properties of watersheds (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, variation in spatial heterogeneity and habitat diversity of freshwater systems, which was identified as one of the main drivers of genetic diversification in P. riparioides (19), is lower in Macaronesian islands than on the continent, due to their volcanic origin and the physical properties of watersheds (20).…”
Section: Resultsmentioning
confidence: 99%
“…IM implements an isolation-with-migration model with two populations and six parameters (theta A , theta 1 , theta 2 ; t, m 1 , m 2 ).The neutral coalescent model involves random mating, a condition that is unlikely to be met in P. riparioides owing to its bisexual gametophytes and putatively high selfing rates (19). We therefore selected one individual from each of 72 localities (40 belonging to the continent and 32 to the island region), as advocated by Lessard and Wakeley (52).…”
Section: Methodsmentioning
confidence: 99%
“…This is best illustrated in the Macaronesian endemic bryophyte flora, wherein endemic species evolved from Neotropical, sub-Saharan Africa, or even eastern Asian ancestors rather than from European or North African ones (Vanderpoorten et al 2010b). Although landscape-scale dispersal limitations were evidenced in a few instances, possibly enhanced by local ecological specialization (Hutsemékers et al 2010), one interpretation for the recruitment of endemics from geographically remote ancestors is that the dispersability of bryophytes precludes the establishment of isolation-by-distance patterns, and hence, opportunities for allopatric speciation, at the scale of tens to hundreds of kilometers.…”
Section: Origin and Evolution Of The Bryophyte Flora From The Pantepumentioning
confidence: 99%
“…there is no retention of deleterious alleles, as in diploid organisms, so that those alleles are eliminated quickly from the genomes of haploid bryophytes (Anderson, 1963). Nevertheless, high levels of genetic diversity in haploid gametophytes have been found as revealed by several kinds of genetic markers, such as RAPDs and isozymes (Cummins & Wyatt, 1981;Wyatt et al, 1989Wyatt et al, , 2005Stenøien & Så stad, 1999), ISSRs (Spagnuolo et al, 2007;Buczkowska et al, 2010), and microsatellites (Wilson & Provan, 2003;Shaw et al, 2008;Hutsemekers et al, 2010). It is suggested that genetic diversity in haploid bryophytes could be maintained by multiple-niche selections (Wyatt et al, 1989), interlocus interaction, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Diploids have also been found in the Brachytheciaceae (Platyhypnidium riparioides (Hedw.) Dixon: Hutsemekers et al, 2010) and Calliergonaceae (Warnstorfia, Scorpidium: Nagl & Ullmann, 1973;Hedenä s, 1989;Fritsch, 1991). Near or total fixation for two alleles per locus per individual leads to the assumption that polyploids in bryophytes are mainly of allopolyploid origin (Så stad, 2005;Shaw, 2009;Karlin et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%